PENGARUH FISCAL STRESS DAN SILPA PADA PENYERAPAN ANGGARAN PADA PEMERINTAH DAERAH DI PROVINSI SUMATERA SELATAN - Elpana, Methasa Cindy; Periansya; Dwitayanti, Yevi (Jurnal Riset Terapan Akuntansi, 2024)
The purpose of this study is to analyze what factors affect Budget Absorption in South Sumatra Province. The independent variables in this study are Fiscal Stress and Budget Calculation Surplus while the dependent variable is Budget Absorption. This study involved all districts / cities in South Sumatra province, namely 17 districts / cities, with saturated sampling criteria. Secondary data used in this study were obtained from the Supreme Audit Agency of the Republic of Indonesia for 5 years. This study uses multiple regression analysis to analyze the data. The results in this study indicate that Fiscal Stress and Budget Calculation Surplus have a significant effect on Budget Absorption in South Sumatra Province in 2018-2022 Government budget absorption in South Sumatra province is influenced by the variables of Fiscal Stress and Budget Calculation Surplus, along with the results of data processing with the IBM SPSS statistical program that has been analyzed. Keywords: Fiscal Stress, Budget Surplus and Budget Absorption